RETRACTED: Exosome-Delivered LncHEIH Promotes Gastric Cancer Progression by Upregulating EZH2 and Stimulating Methylation of the GSDME Promoter - Lu, Yan; Hou, Kaiqing; Li, Mengsen; Wu, Xiaobin; Yuan, Shaochun (Frontiers in Cell and Developmental Biology, 2020)
Gastric cancer is the third leading cause of cancer-related deaths worldwide and is characterized by poor survival and high recurrence rates. Long noncoding RNAs (lncRNAs) have gained considerable attention in recent years as prognostic markers and gene regulators in various cancers. Here, we found that lncHEIH was upregulated in gastric cancer tissues and cell lines and positively correlated with high expression levels of EZH2. Mechanistically, the lncHEIH-EZH2 axis could promote the progression of gastric cancer. In addition, lncHEIH encapsulated in exosomes was released by gastric cancer cells and then absorbed by normal gastric cells. The uptake of lncHEIH resulted in the upregulation of EZH2, which inhibited the expression of the tumour suppressor GSDME by methylation of the GSDME promoter, promoting the malignant transformation of normal gastric cells. Overall, lncHEIH promotes gastric cancer progression by upregulating the expression of EZH2 and reducing the expression of GSDME in normal cells to induce malignant cell proliferation and migration, indicating its potential as a target in gastric cancer therapy.